2019
DOI: 10.3390/nu11071601
|View full text |Cite
|
Sign up to set email alerts
|

The Preventive Effects of Greenshell Mussel (Perna canaliculus) on Early-Stage Metabolic Osteoarthritis in Rats with Diet-Induced Obesity

Abstract: The prevalence of osteoarthritis (OA) is rising worldwide, with the most pronounced increase being in the category of metabolic-associated osteoarthritis (MetOA). This is predicted to worsen with the global rise in aging societies and obesity. To address this health burden, research is being conducted to identify foods that can reduce the incidence or severity of MetOA. Oil from the Greenshell mussel (Perna canaliculus) (GSM), a native New Zealand shellfish, has been successfully used to reduce OA symptoms. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 46 publications
3
19
1
Order By: Relevance
“…The chondroprotective effect of GSM has recently been reported in an experimental model of OA. In this study, serum concentration of the cartilage degradation biomarker CTX-II was signi cantly reduced after GSM powder was added to the diet of rats actively developing metabolic OA [14]. Results from this preliminary study support the potential for an intervention study supplementing human subjects with GSM powder in order to slow the development of OA.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…The chondroprotective effect of GSM has recently been reported in an experimental model of OA. In this study, serum concentration of the cartilage degradation biomarker CTX-II was signi cantly reduced after GSM powder was added to the diet of rats actively developing metabolic OA [14]. Results from this preliminary study support the potential for an intervention study supplementing human subjects with GSM powder in order to slow the development of OA.…”
Section: Introductionsupporting
confidence: 59%
“…To the best of our knowledge, this is the rst randomized controlled trial that will determine the effect of whole meat GSM powder on cartilage metabolism, bone resorption, and in ammation biomarkers in overweight and obese postmenopausal women who at high risk of developing OA. The current study builds on a promising pre-clinical trial [14] which con rmed the chondroprotective effect of GSM powder in an experimental model of metabolic OA by reducing the CTX-II (decreasing type II collagen degradation) without any apparent adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, several studies have reported on the extracts from Perna canaliculus (PC) as a compelling candidate for the treatment of arthritis due to their anti-inflammation effect [ 24 , 25 ]. As such, we planned to compare the effects of ME and PC on the animal arthritis and inflammation models.…”
Section: Introductionmentioning
confidence: 99%
“…The GSM lipid fraction contains a high proportion of omega-3 long-chain (C ≥ 20) polyunsaturated fatty acids ( n -3 LC PUFAs), predominantly (DHA, 22:6 n -3) and eicosapentaenoic acid (EPA, 20:5 n -3), which are split between the triacyglycerol (TAG) and polar lipid (PL) classes [ 2 , 3 ]. These GSM products have been extensively tested in pre-clinical animal studies [ 4 , 5 ]. A recent review has identified a gap in the literature for GSM active ingredients regarding their pharmacokinetics and identification of the bioactive factors responsible for each observed therapeutic effect [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nutraceutical products from GSM (both oil and powders) have been shown to have benefits in human clinical trials on the alleviation of osteo-/rheumatoid-arthritis [ 20 , 21 , 22 ], asthma [ 23 , 24 ], and adverse effects of exercise and/or inflammation [ 25 , 26 ]. With some new animal studies showing novel activity in protecting against cartilage damage in both early-stage and late-stage metabolic osteoarthritis [ 5 ], increasing lean mass accrual in diet-driven obesity, and reducing loss of bone mineral density in osteoporosis [ 27 ]. Due to the low lipid content of mussels (~2%), nutraceutical oils from GSM are produced on an industrial scale either by solvent extraction or by supercritical CO 2 extraction.…”
Section: Introductionmentioning
confidence: 99%